Mastering communication - Stanton, Nicky (Palgrave master series, 2009)
This comprehensive 'how to' book is for anyone wishing to improve their communication skills and knowledge of the way in which communications function in organisations. It covers the skills of speaking, writing, listening and effective reading and provides guidance on telephoning, intervewing and meetings